2020
DOI: 10.1017/jfm.2020.449
|View full text |Cite|
|
Sign up to set email alerts
|

Rayleigh–Taylor instability by segregation in an evaporating multicomponent microdroplet

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 55 publications
0
26
1
Order By: Relevance
“…In recent years, studies on multicomponent droplets have revealed attractive physical phenomena (Lohse & Zhang 2020) induced by the preferential evaporation of individual components or mediated by external vapour sources, e.g. the occurrence of density-driven flows (Edwards et al 2018;Li et al 2019), phase segregation/separation (Li et al 2018;Li et al 2020;Mao et al 2020), the transient Marangoni flow and solutal effects (Christy, Hamamoto & Sefiane 2011), etc. Specifically, in an evaporating multicomponent droplet, the spatiotemporal variation of interfacial mass flux induces the gradients of liquid density, temperature and concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies on multicomponent droplets have revealed attractive physical phenomena (Lohse & Zhang 2020) induced by the preferential evaporation of individual components or mediated by external vapour sources, e.g. the occurrence of density-driven flows (Edwards et al 2018;Li et al 2019), phase segregation/separation (Li et al 2018;Li et al 2020;Mao et al 2020), the transient Marangoni flow and solutal effects (Christy, Hamamoto & Sefiane 2011), etc. Specifically, in an evaporating multicomponent droplet, the spatiotemporal variation of interfacial mass flux induces the gradients of liquid density, temperature and concentration.…”
Section: Introductionmentioning
confidence: 99%
“…2018; Li et al. 2020; Mao et al. 2020), the transient Marangoni flow and solutal effects (Christy, Hamamoto & Sefiane 2011), etc.…”
Section: Introductionmentioning
confidence: 99%
“…To visualize the local details within the segregative patterns, the binary mixture was labelled with two different dyes, Dextran and Nile Red (Li et al 2018). Dextran dissolves preferentially in water, and it was excited by a laser at wavelength 488 nm, while Nile Red is a lipophilic dye that dissolves only in 1,2-hexanediol and was excited by a laser at wavelength 561 nm simultaneously.…”
Section: Fluorescence Image Acquisitionmentioning
confidence: 99%
“…In (partially) volatile multicomponent droplets, in general, phase segregation emerges, as such systems are out of equilibrium. This is due to evaporation (Tan et al 2016;Li et al 2018;Karpitschka 2018;Kim & Stone 2018;Sadafi et al 2020) or dissolution (Dietrich et al 2017), or crystallization (Mailleur et al 2018;Li et al 2020b). Commonly, the emerging segregative patterns lead to a non-volatile shielding or an entrapment, where one liquid on the surface of the droplets covers the others, hindering its further evaporation.…”
Section: Introductionmentioning
confidence: 99%
“…The full phase diagram in the Ra vs M a parameter space is displayed in figure 4d, featuring either pure Rayleigh convection rolls, or pure Marangoni convection rolls, or both at the same time. Also for large Rayleigh numbers the axisymmetry can be broken, and a Rayleigh-Taylor instability can emerge [137].…”
Section: Droplets In Concentration Gradients Emerging From Phase Tran...mentioning
confidence: 99%